Assessment of Ocular Surface Damage during the Course of Type 2 Diabetes Mellitus - Fanglin He; Zhanlin Zhao; Yan Liu; Linna Lu; Yao Fu (Journal of Ophthalmology)
Purpose. To investigate the impact of disease duration on the ocular surface during the course of type 2 diabetes mellitus compared with nondiabetic controls. Methods. One hundred twenty diabetic patients were divided into three groups according to disease duration: less than 5 years, 5–10 years, and over 10 years. All eyes were imaged using a corneal topographer (Oculus Keratograph 5M). Tear film measurements and meibography were also recorded. Meibomian gland changes were scored from 0 to 6 (meiboscore). Results. The noninvasive breakup time first (NIKBUT-1st) and noninvasive breakup time average (NIKBUT-avg) were significantly shorter in the over 10 years diabetic group compared with the control group (P=0.0056  and  P=0.010, resp.). Tear meniscus height (TMH) was significantly lower in the over 10 years diabetic group compared with the control group (P=0.0016) and the 5 years group (P=0.0061). We also found that more patients in the over 10 years diabetic group showed bulbar and limbal hyperemia compared with the control group (bulbar hyperemia: P=0.049; limbal hyperemia: P=0.026). The meiboscore in the over 10 years diabetic group was significantly higher compared with the other three groups (P<0.05). Bulbar hyperemia showed a significant negative correlation with NIKBUT-1st in the over 10 years diabetic group (r=−0.35  and  P<0.05). Conclusion. Ocular surface damage in long-term type 2 diabetes is more severe than that in patients with shorter disease duration.